Synthesis and characterization of mixed oxide pigment Bi1.5Zn0.5CeNbO7 - Těšitelová, Kateřina; Šulcová, Petra; Šnajdarová, Martina (Česká společnost průmyslové chemie, 2016)
This study is focused on the preparation of pigment with general formula Bi1.5Zn0.5CeNbO7 by classical ceramic route in combination with different homogenisation method of initial compounds (hand-milling, dry and wet ball-milling).
Syntéza a charakterizace směsného oxidického pigmentu Bi1.5Zn0.5CeNbO7
Keywords: Mixed Oxide Pigment; Inorganic Pigment; Bi2O3; Different Methods of Homogenization; Colour Properties; směsný oxidický pigment; anorganický pigment; Bi2O3; rozdílné metody homogenizace; barevné vlastnosti